Examining the utility and readiness of mobile and field transportable laboratories for biodefence and global health security-related purposes. Issue 1 (1st January 2018) - Parsons, Andrew; Matero, Pirjo; Adams, Martin; Yeh, Kenneth
ABSTRACT: Mobile and field transportable laboratories have long been used by military and defence, intergovernmental inspections, health, and environmental monitoring agencies. Among the purposes of deploying such laboratories are early warning, forward reconnaissance, on-site investigation, verification, and response. With the advent of technology that has enabled the use of diagnostic equipment in the field and extended transportation capabilities to rapidly deliver these assets and services, mobile and field units have served to further extend networks of existing, fixed laboratories. Case histories of example mobile and field transportable laboratories are compared and discussed including those used by the United States military, Finnish Defence Forces, United Nations, and several mobile and transportable diagnostics laboratories used in response to the 2014 outbreak of Ebola virus in West Africa. Given the often-remote locations to which these laboratories are deployed, they must incorporate a high degree of self-sufficiency, particularly with regard to utilities, and integral biosafety and biosecurity measures. Experienced scientists performing similar technical tasks in fixed laboratories can be employed to support and refine the mobile and field laboratory operations. Mobile and field transportable laboratories are usually national-level assets that require ongoing funding for maintenance, equipping, resupply, and training of personnel in order to maintain a readiness posture for their intended missions. We also examine the cost estimates and sustainment challenges of operating and maintaining these laboratories to provide recommendations and lessons learnt for their practical use and deployment.